Sejarah Pertumbuhan Dan Perkembangan Pendidikan Pada Masa Dinasti Umayyah - Muhammad Faiq Hirzullah; Setiantono - (Institut Agama Islam Sunan Giri Ponorogo, 2023)
This study aims to determine the history of the growth and development of education during the Umyyah Dynasty as the first dynasty as a century of expansion drifting with issues concerning conquest, consolidation and as a multinational and multicultural empire conscious of its needs. Consciously pay great attention to educational issues. So in turn this Umayyah Dynasty is able to grow the various scientific sciences that are now felt useful, especially for the European world that is able to dig and develop it. Education during the reign of the Umayyahs was more developed than in the days of Khulafur Rashidin. The most prominent development of education is on the institutional and science aspects taught. In the institutional aspects have emerged and evolved new educational institutions,And the decline and destruction of the Umayyah Dynasty was caused by many factors, its dignity was: the seizure of power between the royal family, the conflict with Shi'a and Khawarij opposition, ethnic opposition of the North Arab tribes and the South Arab tribes, the incompetence of the caliphs in leading the government and their luxurious living tendencies, the overthrow of the Bani Abbas fully supported by the Bani Hashim.